The Evolutionary Stages of Arabic Calligraphy During Islamic Era/ المراحل التطورية للخط العربي خلال العصور الإسلامية - Duaa Mohammed Alashari (Universitas Negeri Malang, 2022)
The Arabic calligraphy has been important since its inception, and the calligraphy, after the brightness of the light of Islam, was given great care by Muslims because by means of Arabic calligraphy the Holy Qur’an was preserved. Because of the Islamic conquests in Arab and non-Arab countries, this led to the development of Arabic calligraphy throughout the Islamic ages. Therefore, this study aims to reveal the role of Islamic eras in developing, refining and rooting Arabic calligraphy. The study also aims to shed light on the evolutionary stages that Arabic calligraphy has gone through. The method used in this study is the descriptive one, as it is compatible with the research directions and objectives. The study concluded that Arabic calligraphy is one of the finest Islamic arts that became famous and spread due to the Islamic conquests in Arab and non-Arab countries. للخط العربي أهميةٍ منذ نشأته، ولقد حظي الخط بعد سٌطوع نور الإسلام بعنايةٍ بالغةٍ من قبل المسلمين لأن بواسطة الخط العربي حفظ القران الكريم. وبسبب الفتوحات الإسلامية في الدول العربية والغير عربية أدى ذلك إلى تطور الخط العربي على مر العصور الإسلامية. لذلك تهدف هذه الدراسة إلى الكشف دور العصور الإسلامية في تطوير وتجويد وتأصيل الخط العربي. كما تهدف الدراسة إلى إلقاء الضوء على المراحل التطورية التي مر بها الخط العربي. المنهج المتبع في هذه الدراسة هو المنهج الوصفي كونه يتناسب مع توجهات البحث وأهدافه. وتوصلت الدراسة إلى أن الخط العربي من أرقى الفنون الإسلامية التي ذاع صيتها وانتشرت بسبب الفتوحات الإسلامية في الدول العربية والغير عربية، وتطور في العصور الإسلامية وأصبح فناً له طابعه الخاص الذي تميز بوحدة الفنية وبوحدة التعبيرية وتنوع في الأساليب الخطية التي لا تتعارض مع الوحدة الإسلامية.